The Karolinska NeuroCOVID study protocol: Neurocognitive impairment, biomarkers and advanced imaging in critical care survivors. Issue 6 (2nd April 2022) - Nelson, David W.; Granberg, Tobias; Andersen, Pia; Jokhadar, Elias; Kåhlin, Jessica; Granström, Anna; Hallinder, Helena; Schening, Anna; Thunborg, Charlotta; Walles, Håkan; Hagman, Göran; Shams‐Latifi, Roya; et al.
Abstract: Background: This is the study plan of the Karolinska NeuroCOVID study, a study of neurocognitive impairment after severe COVID‐19, relating post‐intensive care unit (ICU) cognitive and neurological deficits to biofluid markers and MRI. The COVID‐19 pandemic has posed enormous health challenges to individuals and health‐care systems worldwide. An emerging feature of severe COVID‐19 is that of temporary and extended neurocognitive impairment, exhibiting a myriad of symptoms and signs. The causes of this symptomatology have not yet been fully elucidated. Methods: In this study, we aim to investigate patients treated for severe COVID‐19 in the ICU, as to describe and relate serum‐, plasma‐ and cerebrospinal fluid‐borne molecular and cellular biomarkers of immune activity, coagulopathy, cerebral damage, neuronal inflammation, and degeneration, to the temporal development of structural and functional changes within the brain as evident by serial MRI and extensive cognitive assessments at 3–12 months after ICU discharge. Results: To date, we have performed 51 3‐month follow‐up MRIs in the ICU survivors. Of these, two patients ( 4%) have had incidental findings on brain MRI findings requiring activation of the Incidental Findings Management Plan. Furthermore, the neuropsychological and neurological examinations have so far revealed varying and mixed patterns. Several patients expressed cognitive and/or mental concerns and fatigue, complaints closely related to brain fog. Conclusion: The study goal is to gain a better understanding of the pathological mechanisms and neurological consequences of this new disease, with a special emphasis on neurodegenerative and neuroinflammatory processes, in order to identify targets of intervention and rehabilitation.